Development of a simple clinical score to estimate in-hospital adverse event risk after elective hip arthroplasty: a retrospective cohort study in a high-risk population - Wolf, Matthias; Papathanakis, Dominik; Trefzer, Raphael; Merle, Christian; Walker, Tilman; Deisenhofer, Julian (Archives of orthopaedic and trauma surgery, 2025)
Patients undergoing total hip arthroplasty (THA) in tertiary centres often present with complex comorbidities that increase the risk of perioperative adverse events (AE). While fast-track and outpatient protocols are expanding, reliable risk stratification tools tailored to high-risk European populations remain limited. This study aimed to (1) compare comorbidity burden in a high-risk population to national data, (2) determine incidence and risk factors for in-hospital AE and (3) develop a simple, pragmatic score to identify patients at elevated AE risk.
Gesehen am 16.02.2026